Interpolation theorem for Nikol’skii-Besov type spaceswith mixed metric - Bekmaganbetov, K.A.; Kervenev, K.Ye.; Toleugazy, Ye. (KU Publ., 2020)
In this paper we study the interpolation properties of Nikol’skii-Besov spaces with a dominant mixed derivative and mixed metric with respect to anisotropic and complex interpolation methods. An interpolation theorem is proved for a weighted discrete space of vector-valued sequences l q(A). It is shown that the Nikol’skii-Besov space under study is a retract of the space l q(Lp). Based on the above results, interpolation theorems were obtained for Nikol’skii-Besov spaces with the dominant mixed derivative and mixed metric.
Аралас метрикалы Никольский-Бесов титес кеңістіктер үшін интерполяциялық теорема
Интерполяционная теорема для пространств типа Никольского-Бесова со смешанной метрикой
Keywords: Nikol’skii-Besov type spaces; method of anisotropic interpolation; complex interpolation